Median mandibular flexure—the unique physiological phenomenon of the mandible and its clinical significance in implant restoration - Gao, Jing; Jiang, Lulu; Zhao, Baohong (Frontiers in Bioengineering and Biotechnology, 2023)
Mandibular flexure, characterized by unique biomechanical behaviors such as elastic bending and torsion under functional loading, has emerged as a crucial factor in oral clinical diagnosis and treatment. This paper presents a comprehensive review of the current research status on mandibular flexure, drawing insights from relevant studies retrieved from the PubMed database (www.ncbi.nlm.nih.gov/pubmed), including research conclusions, literature reviews, case reports, and authoritative reference books. This paper thoroughly explores the physiological mechanisms underlying mandibular flexure, discussing different concurrent deformation types and the essential factors influencing this process. Moreover, it explores the profound implications of mandibular flexure on clinical aspects such as bone absorption around dental implants, the precision of prosthesis fabrication, and the selection and design of superstructure materials. Based on the empirical findings, this review provides crucial clinical recommendations. Specifically, it is recommended to exert precise control over the patients mouth opening during impression-taking. Those with a high elastic modulus or bone-tissue-like properties should be prioritized when selecting superstructure materials. Moreover, this review underscores the significance of customizing framework design to accommodate individual variations in facial morphology and occlusal habits. Future research endeavors in this field have the potential to advance clinical diagnosis and treatment approaches, providing opportunities for improvement.